2018
DOI: 10.1075/dujal.18003.oat
|View full text |Cite
|
Sign up to set email alerts
|

Content and Language Integrated Learning in Dutch bilingual education

Abstract: This small-scale observational study explores how Dutch bilingual education history teachers (BHTs) focus on the L2 component in their CLIL-lessons. We observed and rated eight BHTs on five language teaching categories. Results show that Dutch BHTs focus more strongly on using the L2 to teach subject content and that they tend to be less engaged in teaching specific second language topics, such as focus on form or language learning strategies. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Data of the study demonstrated the students' active interaction through different techniques as reflected in Koopman et al (2014), Oattes et al (2018), Van Kampen et al (2018, Tugun et al (2020), Villabona and Cenoz (2021) even in a remote learning setting. Results of studying pedagogical practices showing that students had enough opportunity to use English in CLIL classes contradict with those of other studies stating the challenges of using target language while studying content (Dalton-Puffer, 2007;Mahan et al, 2018;Villabona & Cenoz, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Data of the study demonstrated the students' active interaction through different techniques as reflected in Koopman et al (2014), Oattes et al (2018), Van Kampen et al (2018, Tugun et al (2020), Villabona and Cenoz (2021) even in a remote learning setting. Results of studying pedagogical practices showing that students had enough opportunity to use English in CLIL classes contradict with those of other studies stating the challenges of using target language while studying content (Dalton-Puffer, 2007;Mahan et al, 2018;Villabona & Cenoz, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Finally, it is worth noting the more recent work of Oattes et al (2022), who used three instruments to collect data. First, a quantitative Pedagogical Content Knowledge (PCK) checklist was used to record the frequency and quality with which particular PCK items were used, supplemented by qualitative data software to analyze fourteen key items from twelve paired lessons to distinguish differences and similarities in the language of instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they used the Protocol for the Assessment of Teaching History (PATH), designed by Van Hover et al (2012), with the six categories it includes with the aim of improving instruction. In addition, for the quantitative part, the assessment scores of the 24 observed classes were analyzed using the SPSS software to calculate descriptive statistics, quantifying the differences between the applications of the PCK categories (Oattes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To triangulate the results of the experiment, after the first and last interventions, semi-structured interviews were also conducted with three participants to collect qualitative data on changes in their views about research (see Figure 1). Thematic content analysis was performed on the interview data to ascertain changes in participants' research motivation (Oattes et al, 2022).…”
Section: Methodsmentioning
confidence: 99%